PENGARUH CITRA PERUSAHAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN ANGGOTA (Studi pada Kospin Jasa) - Alfian Wijanarko; Devi Krisnawati (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
To determine the effect of company image and service quality on member satisfaction Kospin Jasa. The research method uses qualitative and quantitative descriptive analysis, the analysis model used is linear regression both simply and multiple. The study population was all 116 members of the Kospin Jasa. The sampling technique of this study used simple random sampling. This study uses a sample size with the Slovin formula and obtained as many as 55 respondents. Result the of company image and service quality have a positive and significant effect on satisfaction of Kospin Jasa members both partially and simultaneous.